Kejadian Diare dan Pemberian Makanan pada Bayi Usia 1-6 Bulan - Elfira Nurul Aini; Zumrotul Umi Azizah (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2017)
Abstract: The purpose of this study was to analyze diarrhea-based diarrhea occurrences for infantsaged 1 month to 6 months. The study design was using retrospective case-control, with a population of47 babies. Sampling using Slovin calculation method is 42 infants aged 1 month to 6 months that meetinclusion criteria. The research instrument used questionnaire then data were analyzed using FisherExact Test result p-value <a (0,006 <0,05) showed there was the difference of diarrhea occurrencebased on food given to infant age 1 month up to 6